1969
DOI: 10.2118/2199-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Bay Marchand Pressure Maintenance Project Unique Challenges of an Offshore, Sea-Water Injection System

Abstract: The Bay Marchand Pressure Maintenance Project Unique Challenges of an Offshore, Project Unique Challenges of an Offshore, Sea-Water Injection System Extreme formation damage caused by the injection fluid; reservoir sands that broke down under injection; severe corrosion; and mechanical problems all spelled trouble in this large pressure maintenance project. Changes, based on test results, have turned it into a successful sea-water injection system. Introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Moreover, McCune implies that at a filtration down to 0.45 micron all permeability losses are attributed to chemicar-reactions. This is in contradiction with what Jordan et al [12] stated about iron particles. Most probably, McCune was well aware of the impact of submicron particles on formation damage, but his major concern may have been the economics of water treatment.…”
contrasting
confidence: 75%
See 2 more Smart Citations
“…Moreover, McCune implies that at a filtration down to 0.45 micron all permeability losses are attributed to chemicar-reactions. This is in contradiction with what Jordan et al [12] stated about iron particles. Most probably, McCune was well aware of the impact of submicron particles on formation damage, but his major concern may have been the economics of water treatment.…”
contrasting
confidence: 75%
“…The work of Jordan et al [12] dealt with an offshore sea-water injection project where the brine was filtered through 0.45 micron filters prior to injection. Even after filtering, Jordan et al found that "colloidal-size" iron particles were the primary plugging agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two excellent examples of the application of on-site core-test results for specific fields are given by Farley and Redline 10 and Jordan et ai. 11 …”
Section: Discussionmentioning
confidence: 99%
“…56 described the solution of a large number of problems in a pressure maintenance operation in which sea water was used to enhance water encroachment.…”
Section: Gas Cycling Of Condensate Reservoirsmentioning
confidence: 99%